Modern Mandarin Chinese grammar : a practical guide - Ross, Claudia; Ma, Jing-heng Sheng (New York : Routledge, 2014)
"Modern Mandarin Chinese Grammar is an innovative reference guide to Mandarin Chinese, combining traditional and function-based grammar in a single volume.Divided into two sections closely linked by extensive cross-references, it covers:traditional grammatical categories such as phrase order, nouns, verbs and specifiers language functions and notions such as communication strategies, giving and seeking information, expressing apologies, regrets and sympathies.With all grammar points and functions richly illustrated with examples, and a strong emphasis on contemporary usage, the main features of this Grammar include examples in simplified characters, traditional characters, and romanization (Pinyin) as well as an emphasis on areas of particular difficulty for learners of Mandarin Chinese.This is the ideal reference grammar for learners of Mandarin Chinese at all levels, from elementary to advanced. No prior knowledge of grammatical terminology is assumed and a glossary of grammatical terms is provided. Featuring related exercises and activities, this Grammar is accompanied by the Modern Mandarin Chinese Grammar Workbook"--
Includes index.
Keywords: Chinese language -- Grammar; Mandarin dialects -- Grammar; Mandarin dialects -- Self-instruction.; Chinese language -- Textbooks for foreign speakers -- English; FOREIGN LANGUAGE STUDY / General; FOREIGN LANGUAGE STUDY / Chinese; LANGUAGE ARTS & DISCIPLINES / General